Pengaruh Klaim Online Terhadap Tingkat Kepuasan Peserta Bpjs Ketenagakerjaan Cabang Meulaboh - Sri Putri Ayuni Mulia (Cattleya Darmaya Fortuna, 2021)
This study was conducted to determine the effect of online claims on the level of BPJS Employment Participants in the Meulaboh Branch. The method used is a quantitative method. This study uses primary data, namely distributing questionnaires, distributing questionnaires online by sharing a google link from the use of wattsap social media. secondary data were obtained from research method books, journals, participant documents and related literature. The research was conducted at BPJS Employment Meulaboh Branch. Research samples from BPJS Employment Meulaboh Branch participants who made online claims. The number of respondents in this study which was used as a sample was 41 respondents. The research sample was taken with the type of probability sampling using the simple random sampling method. The data analysis used is the validity test, reliability test, simple linear regression test, hypothesis testing using t test, and the use of the SPSS version of the application 20.0. The results of the simple linear regression analysis show that Rsquare is 0.710 nominal. This indicates that the influence of the Online Claims variable (X) on the level of participants (Y), which is 71%, not 100%, the remaining 29% is influenced by the factors discussed in this study. From the hypothesis of using the t test, it is known that the online claim value is significant 0.000<0.5 value tcount>ttable (9.777>2.02439) from these results it is concluded that there is a significant influence between online claims on the satisfaction level of BPJS Ketenagakerjaan participants Meulaboh Branch.